Nutritional, medicinal, and ethnopharmacological properties of apricot vine, Landolphia buchananii (Hallier f.) Stapf: A narrative review. - Alfred Maroyi (Student's Journal of Health Research Africa, 2026)
Wild edible plants such as Landolphia buchananii (Hallier f.) Stapf provide dietary diversity, thereby enhancing overall health and nutrition of local communities. The present study was aimed at reviewing the nutritional, medicinal, and ethnopharmacological properties of L. buchananii. This study is based on literature obtained from scientific databases such as SpringerLink, PubMed, Scopus, Web of Science, Google Scholar, ScienceDirect, and SciELO, as well as literature obtained from pre-electronic sources such as books, book chapters, and other scientific publications obtained from the university library. This research showed that the fruit pulp of L. buchananii is a good source of energy, classic nutrients, minerals and nutritionally important amino acids. The species is also characterized by alkaloids, flavonoids, steroids, saponins, cardiac glycosides, phenolics and terpenoids. The bark, roots and leaves of L. buchananii are used as molluscicides and traditional medicine against bilharzia, malaria, stomach problems, andrological disorders, backache, gastro-intestinal diseases, gonorrhoea, gynaecological disorders, hernia, joint pain, urinogenital disorders and wounds. The fruit and stem bark extracts of L. buchananii demonstrated antinociceptive, antioxidant, antipyretic, and cytotoxicity activities. Landolphia buchananii has the potential to enhance nutrition and primary healthcare of local communities in tropical Africa. Future research on L. buchananii should focus on detailed nutritional, phytochemical, pharmacological, and toxicological evaluations of the species.